Navigating the Twisted Path of Delusional Disorder: A Patient Case Study - Ans Waseem, Mirrat Gul Butt, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Delusional disorder of the jealous type is a rare psychiatric condition characterized by persistent and unfounded beliefs that impair functionality and compromise relationships. This case study explores the presentation, management, and potential treatment outcomes for a patient experiencing an acute episode of Delusional Disorder. Aim: To assess the effectiveness of Cognitive behavioural Therapy in modifying delusional beliefs. Method: Cognitive behavioural therapy using psychoeducation, activity scheduling, trigger management, evidence gathering, reality testing, behavioural experiments, reasoning skills, 3C's, and verbal challenges. Results: The findings suggest that CBT techniques may be beneficial in managing Delusional Disorder, particularly the jealous type. This is evidenced by the significant improvement observed in the patient. Implications: Unawareness of Delusional Disorder can lead to misinterpretations as domestic disputes, delaying crucial interventions. Early diagnosis and treatment can help control symptoms and potentially prevent dangerous actions by the patient. Conclusion: The patient's significant improvement suggests that CBT may be a valuable tool for addressing delusional beliefs and associated disruptions. This finding highlights the need for further research to explore the broader applicability of CBT in treating various presentations of Delusional Disorder. Keywords: Delusional disorder, cognitive behavioural therapy, jealous paranoia.